The Relation Between Perceived Stigma And Social Support Among Substance Abusers In Pusat Pemulihan Penagihan Narkotik (Puspen), Karangan, Kedah - Pradeep Raj A/L Nadaraja
The present study was conducted to identify the effects of social support on the perceived stigma among substance abusers in a specified drug rehabilitation center (PUSPEN) in Karangan. Out of 621 people, 234 respondents were selected to participate in this survey, whom consists of the victims in PUSPEN aged 13 to 21 years, their parents and the officers in the rehabilitation center. Three objectives created in this study were answered through quantitative and correlational research design. The collected data were analyzed using descriptive analysis method or to see the proportion for the demographic factor on a regular basis, multiple regression analysis and correlation coefficient analysis by statistical packages for the social science (SPSS). The results obtained showed the higher respondents are from age group 15-25, majority male and Malay, married and mostly are degree holders. It is also notable that highest respondents experience in handling substance abuser are more than 15 years, while having experience more than 10 years in attending course related substance abuse. When identifying the interconnection between social support and perceived stigma among substance abusers in rehabilitation center, among three tested group, the positively influenced group was family, followed by friends and least by society which is surrounding people. Further, there are six independent variables were tested to identify the effects on perceived stigma including blame, stereotypes of dangerousness and predictability, connection and knowledge, knowledge of substance and mental abuse problem, media portrayal and ethnicity, race and culture. Result obtained had shown only stereotype of dangerousness and predictability had positive influence towards perceived stigma, while other independent variable is insignificant with the dependent variable in this study.